Stargirl - Spinelli, Jerry (New York Ember, 2000)
In this story about the perils of popularity, the courage of nonconformity, and the thrill of first love, an eccentric student named Stargirl changes Mica High School forever.
Keywords: High schools -- Popularity -- Individuality